The Influence of Supply Chain Management on Company Performance (Literature Study) - Sari, Ayu Kurnia; Saputra, Hendra (International Conference on Sciences Development and Technology, 2023)
The purpose of this study is to analyze the effect of supply chain management on company performance. supply chain management is the process of integrating business processes between interconnected networks of suppliers, manufacturers, distribution centers, and retailers to improve the flow of goods, services, and information from suppliers to end customers while reducing costs throughout the system and maintaining service levels. Performance is the ability of workers to produce results. Company performance is something that a business produces over time in accordance with established standards. This study uses a type of causal research. The results of this study state that the effect of Supply Chain Management on Company Performance is accepted based on the findings of the analysis and discussion. This is based on the results of the t test, namely Supply Chain Management with t count> t table which shows that Ha is accepted and Ho is rejected. This shows that the variable Management of Supply Chain has a positive and significant effect on the Company's performance variable.